Feasibility study of a new attached multi-loop CO2 heat pipe for bridge deck de-icing using geothermal energy. (1st December 2020) - Lei, Gang; Yu, Xinbao; Li, Teng; Habibzadeh-Bigdarvish, Omid; Wang, Xiang; Mrinal, Manjarik; Luo, Cheng
Abstract: Heated bridge using CO2 heat pipe with geothermal energy as its heating source is a sustainable and environmentally friendly alternative to conventional chemical de-icers, which corrode the bridges and pollute the environment. However, in previous studies, the heat pipe was embedded in the bridge deck for heating and is only applicable to new bridges. In this study, a new attached multi-loop heat pipe system was developed to be used with ground heat exchangers for heating existing bridges. The heat pipe system, using CO2 as the heat transfer fluid, consists of an evaporator pipe and a manifold pipe with five pipe branches. A parametric study was first conducted on the system in a freezer box at controlled freezing temperatures to determine the optimum CO2 pressure and pipe inclination angle. Then the optimized heat pipe system was attached to the bottom surface of a concrete slab and covered with fiberglass and geofoam insulation. A water bath capable of supplying hot water similar to that from the ground heat exchanger was connected to the evaporator pipe as the heating source. The slab was heated at two freezing temperatures of −3.89 °C and −6.67 °C with the water bath temperature ranging from 25 to 45 °C. A 1-D heat transfer model using a finite difference method (FDM) was developed for the heat transfer analyses of the concrete slab. The average convective heat transfer coefficient ( h value) of each test was back-calculated from the FDM model. Results show that an average 28.3% of the supplied heat energy was transferred to the slab surface, and the surface heat flux ranged from 92.8 to 140.3 W/m 2 . Compared with previous studies, the new CO2 heat pipe is feasible and efficient as a heating system attached to existing bridge decks for de-icing.